Phenotypic and molecular characterization of the bacterial causal agents of sugar beet soft rot and vascular necrosis disease in Southeastern Iran - Rezaee Danesh, Y.; Rastgou, M.; Kariman, K. (International Journal of Agricultural Technology, 2021)
The bacterial soft rot and vascular necrosis disease in sugar beet (Beta vulgaris var. saccharifera) can be caused by different bacteria such as Pectobacterium betavasculorum and P. carotovorum subsp. carotovorum. During the 2018-2019 growing season, tissue samples from symptomatic sugar beet plants were collected from sugar beet growing areas in Kerman province, southeastern Iran. Totally, thirty-one bacterial isolates were isolated from the symptomatic tissues, of which nineteen isolates were identified as Pectobacterium spp., nine isolates as Bacillus spp. and three isolates as Flavobacterium spp. based on the phenotypic and biochemical tests. Pectobacterium isolates were further characterized by PCR amplification (using the EXPCCF/EXPCCR primer set) and genomic fingerprinting by rep-PCR. Only 27% of the Pectobacterium isolates were identified as P. carotovorum, while 73% of the isolates were identified as P. betavasculorum. Artificial inoculation of isolates into the wounded sugar beet petioles led to black streaking, root rot and vascular necrosis from which the same bacterial isolates were re-isolated and identified. PCR assays using BOX and ERIC primers, and combined assays clearly differentiated the bacterial isolates, indicating high variability among the isolates. The results shed light on the bacterial causal agents of the sugar beet soft rot and vascular necrosis disease in southeastren Iran, identifying Pectobacterium isolates as the main causal agents (61% of all isolates), and uncovered the phenotypic/genetic variability among the bacterial isolates